EFFECT OF SAMBILOTO EXTRACT (Andrographis paniculata Nees ) ON HISTOPATHOLOGICAL DISCUSSION OF WHITE RATS (Rattus norvegicus) HIPERKOLESTEROLEMIA MODELS - Lorenza Abatan; Derri Tallo Manafe (Universitas Nusa Cendana, 2026)
Introduction: Hypercholesterolemia is a state which can increase free radicals in the body. Sambiloto has antioxidant and anti-inflammation effects that will bind with the free radicals. Methods: This research is a laboratory experimental study with the approach of true experimental design post-test with control group applied to the treatment and control group. The sampling technique is using randomized probability sampling. Samples divided into 6 groups consisted of normal control group, negative control group, positive control group and 3 groups of applying the extract in several doses. Results: Bivariate analysis results shows there is a significant effect on sambiloto extract giving with the jejunum histopathological image on wistar strain white rats (Rattus norvegicus) exposed to hypercholesteremia model with the significance value of p= 0,001 (p<0,05). Discussion: Administration of Sambiloto extract at a dose of 800 mg/kgBB has a significant effect in repairing damage to the jejunum of white rats due to hypercholesterolemia. Sambiloto has antidislipidemia, antioxidant and anti-inflammatory effects. Andrographolid increases HDL levels by increasing the activity of lecithin cholesterol acyl transferase (LCAT). Conclusion: There is a significant result on sambiloto extract giving with the jejunum histopathological image on wistar strain white rats (Rattus norvegicus) exposed to hypercholesteremia model.